La schizofrenia è una malattia genetica? Considerazioni a margine di una lettera alla rivista “Nature” - Fargnoli, Francesco; Belli, Simone; Zanobini, Valentina; Bisconti, Paola; Fargnoli, Domenico (Il sogno della farfalla, 2012)
The idea that schizophrenia is a genetic illness is being endorsed and disseminated not only by the mass media but also by prestigious specialist journals. This is due to an acritical application of the reductionist method, which is a basic characteristic of molecular biology itself, to psychiatry. If we analyze the literature on the genetics of schizophrenia we actually notice that, with the decline of the idea of a monogenetic origin, the studies related to poligeny, that is the interaction of numerous genes “by small effect”, provide data whose interpretation is extremely controversial. Moreover, for over a century, a sector of psychiatric research with a psychopathological orientation has established itself and on the basis of observation and clinical experience has questioned the concept that there is a Defekt resulting from some unknown organic process. Even the hypothesis that the presumed genetic anomaly which causes schizophrenia is related to an altered cortical connectivity is too generic given that it can be applied to other pathologies as well, such as Rett syndrome, epilepsy or autism, and is not supported by the knowledge we have regarding synaptogenetic processes.